Bacillus subtilis bacteriophage SPP1 hexameric DNA helicase, G40P, interacts with forked DNA - Ayora, Silvia (Oxford University Press, 2002)
SPP1-encoded replicative DNA helicase gene 40 product (G40P) is an essential product for phage replication. Hexameric G40P, in the presence of AMP-PNP, preferentially binds unstructured single-stranded (ss)DNA in a sequence-independent manner. The efficiency of ssDNA binding, nucleotide hydrolysis and the unwinding activity of G40P are affected in a different manner by different nucleotide cofactors. Nuclease protection studies suggest that G40P protects the 5′ tail of a forked molecule, and the duplex region at the junction against exonuclease attack. G40P does not protect the 3′ tail of a forked molecule from exonuclease attack. By using electron microscopy we confirm that the ssDNA transverses the centre of the hexameric ring. Our results show that hexameric G40P DNA helicase encircles the 5′ tail, interacts with the duplex DNA at the ss–double-stranded DNA junction and excludes the 3′ tail of the forked DNA.